Analisis Isi International Luxury Hotel di Bandung Berdasarkan TripAdvisor dan Agoda - Wiastuti, Rachel Dyah; Wiliam, Naomi Hosana (Universitas Pendidikan Indonesia, 2018)
This study aims to determine the customer satisfaction factors and dissatisfaction factors for International Luxury Hotels in Bandung based on online reviews in TripAdvisor and Agoda platform. There are two hotels as research objects; Sheraton Bandung Hotel and Towers and InterContinental Bandung Dago Pakar. Content analysis techniques were conduct by analyzing 854 reviews representing consumer satisfaction and 30 reviews representing consumer dissatisfaction, obtained from two hotel platforms; TripAdvisor and Agoda. Â The results reveal 12 satisfaction factors; room quality, employee, food and beverages product, view and ambience, facilities, service quality, cleanliness, location, design, value, internet, parking area, and security. Meanwhile there are 12 dissatisfaction factors; operation issue, cleanliness, room quality, facilities, bathroom quality, service quality, employee, lack of quietness, accessibility and location, price, food and beverage products, and security.